Fredholm boundary-value problem in Sobolev – Slobodetsky spaces - Mikhailets, V. A.; Skorobohach , T. B. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.927 We investigate the most general class of linear one-dimensional boundary value problems whose solutions range over a given Sobolev – Slobodetsky space. We find necessary and sufficient conditions for the unique solvability of such problems and prove a criterion of continuity of their solutions with respect to a parameter in this space.